Role of Caribbean Islands in the diversification and biogeography of Neotropical Heraclides swallowtails. (23rd July 2014) - Lewis, Delano S.; Sperling, Felix A. H.; Nakahara, Shinichi; Cotton, Adam M.; Kawahara, Akito Y.; Condamine, Fabien L.
Abstract: Numerous hypotheses on the evolution of Neotropical biodiversity have stimulated research to provide a better understanding of diversity dynamics and distribution patterns of the region. However, few studies integrate molecular and morphological data with complete sampling of a Neotropical group, and so there has been little synthesis of the multiple processes governing biodiversity through space and time. Here, a total‐evidence phylogenetic approach is used to reconstruct the evolutionary history of the butterfly subgenus Heraclides . We used DNA sequences for two mitochondrial genes and one nuclear gene and coded 133 morphological characters of larvae and adults. A robust and well‐resolved phylogeny was obtained using several analytical approaches, while molecular dating and biogeographical analyses indicated an early Miocene origin (22 Mya) in the Caribbean Islands. We inferred six independent dispersal events from the Caribbean to the mainland, and three from the mainland to the Caribbean, and we suggest that cooling climates with decreasing sea levels may have contributed to these events. The time‐calibrated tree is best explained by a museum model of diversity in which both speciation and extinction rates remained constant through time. By assessing both continental and fine‐scale biodiversity patterns, this study provides new findings, for instance that islands may act as source of diversity rather than as a sink, to explain spatio‐temporal macroevolutionary processes within the Neotropical region.